Adding a new piece to the puzzle of Cosmocercidae evolutionary relationships: genetic characterization of Aplectana pella parasitic in Osteocephalus cabrerai from Amazon Region - Jorge Kevin Silva Neves; Gabriel Lima Rebêlo; Adriano José Silva Félix; Scott Lyell Gardner; Arnaldo Maldonado Júnior; Carlos Eduardo Costa-Campos; Francisco Tiago Vasconcelos Melo (Revista Brasileira de Parasitologia Veterinária)
Abstract Aplectana comprises species of gastrointestinal helminths commonly found parasitizing amphibians and reptiles worldwide. However, most species of the genus are described based only on morphological traits. During helminthological surveys, we found nematodes identified as Aplectana pella parasitizing the hylid frog Osteocephalus cabrerai from the same locality as the original description. We provided the first nucleotide sequence of ribosomal gene 18S rDNA for Aplectana pella and established the species' phylogenetic position between representatives of Cosmocercidae. A pairwise genetic comparison between A. pella and its congeners revealed a low genetic divergence. We found that our sequences clustered with species of Cosmocerca, reinforcing the hypothesis that representatives of the genus Aplectana do not form a monophyletic group.